Determinan Motivasi Wajib Pajak Dalam Memenuhi Kewajiban Perpajakan Pada Wajib Pajak Pekerja Bebas Di Tangerang Selatan - Nur Anggraini; Eva Herianti (Institut Bisnis dan Informatika Kesatuan, 2022)
This research aims to examine and analyze the effect of the self- assessment system, modernization of the administration system, tax awareness and tax audit on the motivation of taxpayers to fulfill their tax obligations. This research is a quantitative research using primary data through questionnaires to free worker taxpayers in the South Tangerang area. This research uses SEM Partial Least Square analysis method with SmartPLS 3.0 analysis tool. Sampling method using the Lemeshow formula (1997) and produced 70 respondents but the data processed were 63 respondents. The results of this study indicate that: The application of the self-assessment system (X1) affects significant the motivation of taxpayers in fulfilling their tax obligations; Modernization of the Administration system (X2) has an effect significant on the motivation of taxpayers in fulfilling their tax obligations; Tax Awareness (X3) affects significant the motivation of taxpayers in fulfilling tax obligations; Tax audit (X4) has effects but not significant on taxpayer motivation in fulfilling tax obligations. Keywords: Self Assessment System Implementation, Administrative System Modernization, Tax Awareness, Tax Audit, Taxpayer Motivation in Fulfilling Tax Obligations.